Econometric Modelling of UK Aggregate Investment: The Role of Profits and Uncertainty - Alan Carruth; Andy Dickerson; Andrew Henley (University of Kent, Department of Economics, 1998)
This paper focuses on the determinants of aggregate investment spending in the UK for the industrial and commercial company (ICC) sector. It complements recent work by Cuthbertson and Gasparro (1995), who study an augmented Tobin's q model of investment in the manufacturing sector. Important focal points of our analysis are a role for real profits (internal funds), which allow firms to combat liquidity constraints when access to capital markets is not perfect, Chirinko (1987), and the impact of irreversibility and uncertainty in determining aggregate investment spending. Earlier work on manufacturing investment by Bean (1981a) developed a dynamic, error correction specification based on the flexible accelerator model. Following Cuthbertson and Gasparro we use multivariate cointegration techniques to discover a parsimonious dynamic model, which can explain the 1980s and early 1990s investment experience of the ICC sector. Our results show that a model based on investment and output alone does not cointegrate, and a short-run dynamic model of these variables suffers from heteroscedasticity. This may be consistent with the idea that increased (uncontrolled for) uncertainty has led to increased volatility in investment. The possibility that movements in the real price of gold reflect uncertainty in financial and other traded commodity markets is explored. Investigation of this more general model indicates that real profits and the real price of gold can enhance the explanation of investment spending by the ICC sector.
Keywords: E2; 330; Aggregate investment; real profits; uncertainty; Investition; Gewinn; Risiko; Ökonometrisches Makromodell; Großbritannien